Analisis Semiotika Makna Budaya Lokal dalam Iklan Rokok Djarum 76 Versi “Indonesia Adalah Kita” - Zamzanaria, Annisa; Susanti , Neila; Abidin, Syahrul (Medan Resource Center, 2022)
This article aims to discuss the semiotic analysis of local cultural meanings in the Djarum 76 cigarette advertisement “Indonesia Is Us” Version. In order to fully and in-depth reveal the problems in this research, this study uses the Charles Sanders Peirce model of semiotic analysis by analyzing the signs contained in the ad impressions which are analyzed in three stages, namely the sign (sign), sign reference (object), and use of signs (interpretants). A qualitative approach is the approach that the authors use in this study using documentation and non-participant observation methods. The results of the study show that in the Djarum 76 cigarette ad there is a diversity of Indonesian culture displayed in the ad. Djarum 76 cigarette advertisements include thematic cigarette advertisements that are adapted to social, political and cultural phenomena that occur in the midst of society and it is common knowledge that themes like this are widely used as ideas in making cigarette advertisements today even though the contents are much different and there is no This has to do with